Generalized crossed modules and group-groupoids - Gursoy, Mustafa Habil; Aslan, Hatice; Icen, Ilhan (Tubitak Scientific & Technological Research Council Turkey, 2017)
In this present work, we present the concept of a crossed module over generalized groups and we call it a generalized crossed module. We also define a generalized group-groupoid. Furthermore, we show that the category of generalized crossed modules is equivalent to that of generalized group-groupoids whose object sets are abelian generalized group.
Keywords: Groupoid; crossed module; generalized group